Exploring Fintech’s Intervening Role and its Impact on Financial Decisions in SMEs in Lombok - Siti Aisyah Hidayati; Sri Wahyulina; Embun Suryani; Siti Sofiyah; Erick Widodo (Jurnal Ilmiah Manajemen Kesatuan, 2026)
Small and Medium Enterprises (SMEs) have a crucial role in the economy, but they continue to encounter challenges in financial decisions because of behavioral and managerial influences. The swift growth of fintech provides possible ways to enhance efficiency and the quality of financial decisions for SMEs. This research seeks to examine how financial knowledge and financial attitudes influence financial decisions, with fintech serving as an intervening variable, among SMEs on Lombok Island, West Nusa Tenggara. This research utilizes a quantitative method featuring an explanatory design. The sampling approach employs non-probability sampling through a judgment sampling method, targeting SMEs involved in the pottery craft sector with export operations, yielding 41 SMEs as research subjects. The findings show that financial knowledge and financial attitude positively and significantly impact the utilization of fintech. Fintech has been shown to influence how financial knowledge impacts financial decisions, yet it does not influence how financial attitude affects those decisions. Moreover, the utilization of fintech positively and significantly influences financial decisions. Fintech significantly contributes to enhancing the impact of financial knowledge on the financial decisions of SMEs.